Utilization of Google Meet Application to Improve Interaction Between Lecturers and Students in Learning at BKPI Students, Wiralodra University, Indramayu - Arinie Falhah; Rizqi Fadli; Didik Himmawan (Al-Ard: Journal of Education, 2025)
This research discusses the use of Google Meet media for the interaction of BKPI students and lecturers at Wiralodra University. The purpose of this research is to find out how the use of Google Meet media affects the interaction between students and lecturers at BKPI Wiralodra University, the factors that influence students' interest in learning, and what the advantages and disadvantages of using Google Meet media are. This research is qualitative, with data described descriptively regarding the use of Google Meet media. The results obtained in this research show that Google Meet is less useful and not effective as a medium for conveying open material. Students are less interested in using Google Meet as a bold learning medium because it is difficult to accept the material being taught, which affects students' interest in learning. Factors that can influence students' interest in learning are media, learning strategies, motivation, students' curious attitude, and the surrounding environment. There are advantages and disadvantages that Google Meet media has for students' learning interests.